2022
DOI: 10.1111/jmwh.13375
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant and Postpartum Women's Perceptions of Barriers to and Enablers of Physical Activity During Pregnancy: A Qualitative Systematic Review

Abstract: Introduction Physical activity throughout pregnancy has been shown to have health benefits for the pregnant person, including reductions in the risk of preeclampsia and gestational weight gain and improvements in blood pressure regulation. Despite the benefits, many pregnant women do not meet the guidelines for physical activity throughout pregnancy. Therefore, it is important to determine what influences women's activity levels during pregnancy. This systematic review of the qualitative literature aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…We found a trend towards greater effectiveness when physical activity targeted at-risk women with a history of depression or elevated depression symptoms during the perinatal period [ 46 ]. However, women may be less likely to undertake exercise due to the symptoms of depression (e.g., less energy, fatigue), which can be an added barrier for women to exercise during pregnancy [ 61 ]. Regarding the type of the exercise activity, our study cannot recommend any intervention in favour of others, but most trials were aerobic in nature [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a trend towards greater effectiveness when physical activity targeted at-risk women with a history of depression or elevated depression symptoms during the perinatal period [ 46 ]. However, women may be less likely to undertake exercise due to the symptoms of depression (e.g., less energy, fatigue), which can be an added barrier for women to exercise during pregnancy [ 61 ]. Regarding the type of the exercise activity, our study cannot recommend any intervention in favour of others, but most trials were aerobic in nature [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this speculation, Teede et al 's [14] recent review of interventions to promote healthy gestational weight gain found that diet only interventions led to more favorable (i.e., less) gestational weight than PA interventions, diet with PA interventions, or mixed interventions. Indeed, the challenges related to increasing PA are substantial [49] and often requiring adding in a new behavior that may be challenging and time-consuming versus making modifications to existing behaviors, as is the case for diet. Behavioral intervention participants in our study improved their diet quality, vegetable intake, and % of grains that were whole grains, suggesting they were able to make small but meaningful changes to their diet.…”
Section: Discussionmentioning
confidence: 99%
“…According to Green (1991), the minimum required sample size for multiple linear regression can be estimated using the formula n > 50 + 8 m , where m is the number of predictors. Based on the literature review, the predictors of physical activity were assumed to be self‐efficacy (Yu et al, 2023), knowledge (McKeough et al, 2022), social support (Grenier et al, 2021), age (Jones et al, 2021), education (Jones et al, 2021), occupation (Jones et al, 2021), monthly household income (Janakiraman et al, 2021), attendance at antenatal physical activity classes (Ahmadi et al, 2021), pre‐pregnancy physical activity habits (Janakiraman et al, 2021), and parity (Alaglan et al, 2020). Thus, in the present study, m is 10.…”
Section: Methodsmentioning
confidence: 99%
“…According to Bandura (1977), physical activity is related to physical activity self-efficacy, which refers to individuals' confidence in their ability to learn or engage in physical activities. Apart from physical activity self-efficacy, insufficient knowledge is commonly reported as a barrier preventing pregnant women from engaging in physical activity (McKeough et al, 2022). Social support for physical activity refers to providing instrumental, informational, emotional, and peer support during physical activity (Xiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%